Kadar N Tanah dan Daun serta Klorofil Karet Umur Sembilan Tahun Dengan Penempatan Mulsa Vertikal Pada Rorak - Jefry Hutasoit; Chairani Hanum (Universitas Sumatera Utara, 2015)
Rubber need a lot of water for growth and production. One of the effort to converse soil water through pit and vertical much added palm oil empty fruit bunches to absorb, hold water and increased nutrient. The objective of the research to study N soil and leaf concent also chlorophyll of rubber was nine years old with placement vertical mulch in pit. The research was conducted at PTPN III Kebun Silau Dunia, Silau Kahean District, Serdang Bedagai Regency, North Sumatera with the heigh 60-90 metre above sea levels, began from August until December 2014. The research was arranged with a factorial randomized block design consisted of two factors. The first factor was pit lenght with three levels were 200, 300, 400 cm and second factor was provision of palm oil empty fruit bunches with three levels were 200, 250, 300 Kg. The result showed that provision of palm oil empty fruit bunches 300 Kg increased N soil about 14.84 % but pit lenght and interaction of two factors not significant effect to N soil and leaf also chlorophyll.Keywords: pit, palm oil empty fruit bunches, rubber.